OC-029 Rifaximin Is Efficacious In The Treatment Of Chronic Overt Hepatic Encephalopathy: A Uk Liver Multi-centre Experience. (9th June 2014) - Patel, VC; Orr, J; Sturgeon, J; Habtemariam, Z; Preedy, H; Richardson, P; Aspinall, R; Hudson, M; Shawcross, DL
Abstract : Introduction: Rifaximin-α is a non-absorbable antibiotic increasingly being used for the secondary prevention of recurrent overt hepatic encephalopathy (HE) in the UK. The therapeutic mechanism of rifaximin has yet to be elucidated, with reduction in gut ammonia production postulated. We undertook a UK multi-centre retrospective audit of patients receiving rifaximin therapy for HE in 4 hospitals, two of which are liver transplant units, with the aim of assessing tolerability, impact on HE/liver disease severity and hospitalisation rates. Methods: Patient demographics, concurrent therapy, Child Pugh, MELD, UKELD and number of hospital admissions were collected 3 months prior to initiation of rifaximin therapy and then 3 months following treatment. Results: 170 patients were identified (mean age 57yrs±12; 68% male) over the period 05/2010–03/2013. Three month post treatment outcome data were available for 73 patients (43%); 53 patients (31%) died during the 3 month follow up period. Average duration of treatment was 79 ± 121 days, with therapy well tolerated in 97.6% of patients. 74% were taking concomitant lactulose with 23.5% on rifaximin monotherapy. No cases of Clostridium difficile infection were reported. The most common aetiology was alcohol 90/170 (53%) with 25 (28%) actively drinking . 36 patients (21%) were transplanted during the audit period. The predominant HE phenotype was episodic overt (67%), with persistent overt featuring in 20% and the Parkinsonian phenotype in 6%. Admission data were available for 143/170 (84%) patients with a total of 444 admissions in the 3 months prior to therapy (average admission length 23 ± 25 days). The hospitalisation rate per patient fell significantly from 2.7 ± 3.2 to 1.0 ± 1.8 admissions in the 3 months following initiation of therapy (p < 0.0001) [Figure i ]. HE grade improved significantly following therapy (p < 0.0001) [Figure ii ]. Child Pugh score fell significantly following therapy (p < 0.0001) [Figure iii ], as did MELD and UKELD scores: 15 ± 7 vs. 13 ± 5 (p < 0.03) and 55 ± 6 vs. 51 ± 5 (p < 0.02), respectively. This is noteworthy as the MELD score does not include HE as a parameter and is based on bilirubin, INR and creatinine. Conclusion: Our UK multi-centre experience is that rifaximin is well-tolerated and an efficacious treatment for the secondary prevention of HE. Rifaximin significantly reduced both hospital re-admission rates after 3 months treatment, impacting significantly on the NHS resource burden of HE, and reduced overall liver disease severity raising the possibility that its therapeutic effect may extend beyond reducing gut ammonia production. Disclosure of Interest: V. Patel Grant/research support from: Norgine (UK) Ltd., J. Orr Grant/research support from: Norgine (UK) Ltd., J. Sturgeon: None Declared, Z. Habtemariam: None Declared, H. Preedy: None Declared, P. Richardson Consultant for: Norgine (UK) Ltd., R. Aspinall Consultant for: Norgine (UK) Ltd., M. Hudson Consultant for: Norgine (UK) Ltd., D. Shawcross Grant/research support from: Norgine (UK) Ltd., Consultant for: Norgine (UK) Ltd.